The role of enkephalins in the perioperative period in patients with oropharyngeal cancer - D. N. Vasiliev; D. E. Kulbakin; E. L. Choynzonov; S. V. Avdeev; A. A. Lee; I. P. Puteev; A. V. Pak; A. V. Kushner (Сибирский онкологический журнал)
Postoperative metabolic disorder, namely the development of protein-energy deficiency is one of the challenges in cancer surgery, especially in head and neck surgeries, which are considered the most traumatic. The development of protein-energy deficiency significantly reduces the reparative capabilities of the body and worsens the surgical treatment outcomes. The purpose of the study was to evaluate the effect of stress protection with enkephalin dalargin, as a component of anestheticmanagement, on the severity of catabolic syndrome in the postoperative period in patients with oropharyngeal cancer. Material and methods. The study included 58 patients who underwent surgical treatment for oropharyngeal cancer. The study group consisted of 29 patients who were given a carbohydrate drink, 400 ml in the evening before surgery and 200 ml 2 hours before surgery. Dalargin was administered in the perioperative period. The control group included 29 patients with standard perioperative management. The conditions of performing surgery in both groups were similar. The levels of real energy metabolism, RQ, nitrogen balance, hormonal spectrum and the number of postoperative complications were studied. Results. The combination of pre-carbohydrate loading and dalargin in the perioperative period was characterized by a significantly lower release of stress hormones as components of the surgical stress response. A positive effect on aerobic metabolism and a decrease in the number of postoperative complications were also observed. Conclusion. The proposed technique can be one of the methods of combating the development of the hypercatabolic phase of metabolism, due to the effectiveness of limiting the surgical stress response and regulating carbohydrate metabolism.